2022
DOI: 10.1017/s0950268822001960
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity and antimicrobial use in broiler farms across nine European countries: toward identifying farm-specific options for reducing antimicrobial usage

Abstract: Broiler chickens are among the main livestock sectors worldwide. With individual treatments being inapplicable, contrary to many other animal species, the need for antimicrobial use (AMU) is relatively high. AMU in animals is known to drive the emergence and spread of antimicrobial resistance (AMR). High farm biosecurity standards are a cornerstone for animal health and welfare, as well as food safety, as it protects animals from the introduction and spread of pathogens and therefore the need for AMU. The goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, two studies indibiosecurity practices is a cost-effective strategy for reducing AMU (Table 1). On the other hand, five studies reported an uncertain or spurious association between farm biosecurity and AMU, which could be attributed to confounders such as recent outbreaks, underreporting of AMU, misclassification, or missing information on AMU and/or biosecurity [9,34,36,40,46] (Table 1). Small pig farms resisted colistin and fluoroquinolones, while medium-sized farms showed resistance to streptomycin.…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, two studies indibiosecurity practices is a cost-effective strategy for reducing AMU (Table 1). On the other hand, five studies reported an uncertain or spurious association between farm biosecurity and AMU, which could be attributed to confounders such as recent outbreaks, underreporting of AMU, misclassification, or missing information on AMU and/or biosecurity [9,34,36,40,46] (Table 1). Small pig farms resisted colistin and fluoroquinolones, while medium-sized farms showed resistance to streptomycin.…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
“…Furthermore, two studies indicated that coaching and awareness among farmers could lead to reduced AMU, while a single economic assessment study concluded that implementing biosecurity practices is a cost-effective strategy for reducing AMU (Table 1). On the other hand, five studies reported an uncertain or spurious association between farm biosecurity and AMU, which could be attributed to confounders such as recent outbreaks, underreporting of AMU, misclassification, or missing information on AMU and/or biosecurity [9,34,36,40,46] (Table 1).…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
See 3 more Smart Citations